Construction of allitol synthesis pathway by multi-enzyme coexpression in Escherichia coli and its application in allitol production. (1st May 2015) - Zhu, Yueming; Li, Hongyi; Liu, Pingping; Yang, Jiangang; Zhang, Xueli; Sun, Yuanxia
Abstract: An engineered strain for the conversion of d -fructose to allitol was developed by constructing a multi-enzyme coupling pathway and cofactor recycling system in Escherichia coli . d -Psicose-3-epimerase from Ruminococcus sp. and ribitol dehydrogenase from Klebsiella oxytoca were coexpressed to form the multi-enzyme coupling pathway for allitol production. The cofactor recycling system was constructed using the formate dehydrogenase gene from Candida methylica for continuous NADH supply. The recombinant strain produced 10.62 g/l allitol from 100 mM d -fructose. To increase the intracellular concentration of the substrate, the glucose/fructose facilitator gene from Zymomonas mobilis was incorporated into the engineered strain. The results showed that the allitol yield was enhanced significantly to 16.53 g/l with a conversion rate of 92 %. Through optimizing conversion conditions, allitol was produced effectively on a large scale by the whole-cell biotransformation system; the yield reached 48.62 g/l when 500 mM d -fructose was used as the substrate.